Politics, planning and homes in a world city - Bowie, Duncan (Housing, planning, and design series., 2010)
An insightful study of spatial planning and housing strategy in London, focusing on the period 2000-2008 and the Mayoralty of Ken Livingstone. It presents an analysis of the development of Livingstone's policies and their consequences.